Studi tentang kegiatan pengembangan koleksi terbitan berkala pada Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat - Sri Parti Nurani; Yunus Winoto (IJAL (Indonesian Journal of Academic Librarianship), 2019)
ENGLISH This study aims to determine the periodical collection collection activities. The location of this study was conducted at the Regional Library and Archives Service Office of West Java Province. The method used in this study is a qualitative research method with the technique of collecting data through interviews, observation and documentation studies. Based on the results of the study, it is known that the activities of developing periodical collections in the Library and Archives Office of West Java Province ", namely the stages of collection development which include analysis of user needs, policy making, development of periodical collections, selection, procurement, weeding and evaluation have been carried out by Disusipda Province but not all stages have been carried out optimally, so there still needs to be some improvement in several stages of the collection development. INDONESIA Penelitian ini bertujuan untuk mengetahui kegiatan pengembangan koleksi terbitan berkala. Lokasi penelitian ini dilakukan di Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan Teknik pengmpulan data melalui wawancara, observasi dan studi dokumentasi. Berdasarkan hasil penelitian diketahui bahwa Kegiatan pengembangan koleksi terbitan berkala di Dinas Perpustakaan Dan Kearsipan Propinsi Jawa Baratâ€ yaitu tahapan-tahapan pengembangan koleksi yang meliputi analisis kebutuhan pengguna, pembuatan kebijakan pengembangan koleksi terbitan berkala, seleksi, pengadaan, penyiangan dan evaluasi telah dilakukan oleh pihak Disusipda Provinsi namun belum semua tahapan dilakukan secara optimal, sehinga masih perlu ada beberapa penyempurnaan dalam beberapa tahapan pengembangan koleksi.